IMPLEMENTASI PROGRAM KAMPUNG IKLIM DI KOTA SURAKARTA - Atur Ekharisma Dewi; Maryono Maryono; Budi Warsito (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
Climate Change is one of the global issues of concern and included in the purpose of the SDGs (Action on climate change). This Research aims to know the potential achievement of the sustainability of Climate Village program in Surakarta. This Research is a literature study and observations in the field and questionnaire, interview. This research is taking location at Kampung Iklim Sekip Kadipiro, Sambirejo Kadipiro, Ngemplak Sutan Mojosongo. Kadipiro geographically, most of the region is a fairly large plateau. Kampung Iklim Sekip Kadipiro once received an award at the national level representing Surakarta municipal. Mojosongo Village is the widest urban village in Surakarta City with 5,329 Regional Areas 5,329 (Km2). Physical Condition of Topographic Village of Ngemplak Sutan Village in Mojosongo Sub-District, Jebres Sub-District is located north of Surakarta City, is a hilly area and is the highest plateau in the city of Surakarta. Based on the Geological Map of the Geohidrology Map of Surakarta, it can be seen that the northern rocks of the Mojosongo Village Office are up to Kali Kebo.Indonesia is one of the contributing countries in reducing GHG emissions by creating Program Kampung Iklim (PROKLIM) which is an environmental management activity based on community empowerment . Program Kampung Iklim is one of the efforts to adapt and mitigate climate change by citizens with friendly and environmentally sound activities. Climate Village activities provide additional income for citizens, where planting crops increases food security and reduces household spending. Waste management with 3R concept by Bank Sampah and innovative products produced by residents are able to increase additional income Kampung Iklim program has a local wisdom despite being in urban areas while maximizing the land of the House of page to plant, livestock and produce innovative local food and crafts products. The results of sustainability research are influenced by local figures, women and community roles.Implementation Kampung Iklim in Surakarta municipal has the potential for sustainability.